Effect of aqua-cycling as exercise therapy in the diagnosis of lipedema - Burger, R.; Jung, M.; Becker, J.; Krominus, J.; Lampe, M.; Kleinschmidt, J.; Kleinschmidt, B. (Phlebologie, 2019)
In the following overview, the general advantages of movement interventions in water, within the physical therapy options, in the diagnosis of lip- and lymphoedema are addressed. Due to positive experiences in patients with lymphoedema, case reports concerning the use of aqua cycling in lipoedema are presented, which should trigger further investigations.
Keywords: Lipoedema; Therapy; Exercise; Aqua-Cycling; Aqua-Fitness; Aqua-Jogging; Fascia